A literature review on the use of retrospective LMS data to investigate online Teaching and Learning practices - Spreadborough, Kristal; Glasser, Solange (Pacific Journal of Technology Enhanced Learning, 2022)
Access to high quality education is a cornerstone of social, cultural, and economic recovery after any crisis. This is also true of the global COVID-19 pandemic which has disrupted the pedagogical practices of higher education institutions around the world (Butler-Henderson, Crawford, Rudolph, Lalani, & Sabu, 2020). Digital learning has become the new-norm, and tertiary education institutions have been propelled to innovate their teaching methods by integrating digital learning through the adoption of cost-effective (Al-Maroof & Al-Emran, 2018) and adaptable (Bhat et al., 2018) Learning Management Systems (LMS) (Bervell & Umar, 2017; Cigdem & Ozturk, 2016). In these systems, pedagogical technologies are embedded in an infrastructure that enables administration and management of learning contents, communication, assessment, and collaboration (Washington, 2019). Due to the fact that the fundamental task of LMS is to support digital teaching and learning (El Bahsh & Daoud, 2016), they are some of the most extensively used learning technologies in higher education (Abazi-Bexheti, Jajaga, & Abazi-Alili, 2018). LMS technology is now widely adopted to support face-to-face, blended, and online pedagogical practices. In this context, LMS data provides large-scale capture, processing, and analysis of students’ interactions with the system, with each other, and with their teaching support within the system (Chung, 2014).  LMS data provides a rich resource through which to investigate online learning technologies and behaviours (see, for example, Chung, 2014). Such work is increasingly being done across multiple domains, however no systematic review has yet been conducted which surveys such work - specifically examining retrospective LMS data. This is the goal of the present paper.